3D Seismic reflection and VSP for hydrogeology - Harris, Brett; Urosevic, Milovan; Kepic, Anton (Society of Exploration Geophysics, 2008)
Modern hydrogeology is increasingly depending numerical modeling to simulate impacts of water resource projects tens or hundreds of years into the future. The validity of such numerical models is highly dependent on accurate distribution of key hydrogeological parameters. A combination of 3D seismic reflection and Vertical Seismic Profiling (VSP) offers the potential to create detailed, accurate, hydrostratigraphic frameworks within which physical, chemical and biological properties can be distributed. We provide the outline and outcomes from a systematic research program designed to develop and optimize 3D seismic reflection and VSP techniques tailored for hydrogeology. The test site is located at the Beenyup Waste Water Treatment Plant near a major freeway, where a long term high volume purified waste water injection trial will commence in 2009.